From the Struggle for Independence to the Religious Conflict - Alaverdov, Emilia; Demircioğlu, Aytekin (IGI Global, 2022)
The chapter deals with the chaotic situation of 1990 when the struggle for independence was intermingled with the religious revival in the acute form of radical Islamism and the process was gradually shifting to the revival and activities of political organizations. At the same time, religion was intertwined with politics and criminal activity. In investigating the conflicts in which Islamic radicals were involved, it was very difficult to distinguish the ideology of religious fundamentalism from criminal activities related to drug and arms business, people trafficking, and kidnapping. Crime, in its turn, was directly in the political and power groups that were closely linked to radicals. Thus, the North Caucasus republic, called Chechnya by Russians, appeared directly in the center of Russia's recent history, threatening its state and social security.
Keywords: 5. Gender equality; 8. Economic growth; 16. Peace & justice